Factors influencing the participation of mothers with toddlers in posyandu activities in Kemenangan Tani Village, Medan Tuntungan District - Mujahidin, Mujahidin; Wenti Anggraeni, Wenti; Daeli, Elisa Hotmauli Gratia; Sabri, Ihsan; Ivonne, Ivonne; Muchtar, Muhammad Arafat; Riskaldy, Riskaldy; Dewani , Yunita; Ferdinand, Sahna; Mukhtar, Zulfikri; Reza, Faisal (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Posyandu is a type of community-based health effort (UKBM) which is managed and organized by, for, and with the community in the implementation of health development. Empowering the community to obtain essential health services, accelerating the reduction of maternal and child mortality. This study aims to determine the relationship between knowledge and characteristics of mothers under five with visits to posyandu activities in Kelurahan Kemenangan Tani. This research is an analytic survey with a cross-sectional approach. The population in this study were mothers of children under five at the Kelurahan Kemenangan Tani Posyandu. The sample in this study was 60 respondents with the determination of the number of samples using the slovin formula. The sampling technique used is proportional random sampling with inclusion and exclusion criteria. Data was collected through interviews using a questionnaire. This study used the chi-square statistical test (Confidance Interval (CI) 95%; = 0.05). Multivariate analysis using logistic regression. The results of this study indicate that there is a significant relationship between mother's knowledge and mother's characteristics with the visit of mothers under five in posyandu activities (p < 0.05). The dominant independent variable was education (p= 0.011; PR= 14,903, 95% CI = 1,872-118,660). The conclusion of this study is that there is a significant relationship between mother's knowledge and mother's characteristics with the visit of mothers under five in posyandu activities. The dominant independent variable is education.